Asymmetric Effects of Electricity Consumption and Population Growth on South Africa’s Employment in the Private-Sector - Takentsi, Siyakudumisa; Sibanda, Kin (International Journal of Energy Economics and Policy, 2025)
This paper empirically investigated the relationship between energy consumption, population growth, and unemployment in South Africa over the period from 1990 to 2022, employing the nonlinear autoregressive distributed lag (NARDL) model. The research aims to analyse how fluctuations in energy consumption and demographic changes influence unemployment rates in the country. By examining the long-run and short-run dynamics among these variables, the study seeks to provide insights into the critical role of energy policies and demographic trends in shaping employment outcomes. The study found that electricity consumption has a nonlinear effect on employment, with positive and negative fluctuations impacting employment differently. Population growth showed no significant effect on private-sector employment in both the short and long run. The results suggest that reduced electricity consumption is associated with increased private-sector employment in South Africa, emphasizing the need for targeted energy policy reforms.